ROAD TRANSPORT INFORMATION SYSTEM: A PANACEA FOR ROAD TRANSPORT FACILITY MANAGEMENT IN KATSINA LOCAL GOVERNMENT, KATSINA STATE, NIGERIA - Dabo, Muhammaed Zilkiflu; Yunus, Sulaiman (FUDMA JOURNAL OF SCIENCES, 2020)
This study aimed at examining the spatial pattern of RTF within Katsina Local Government with a view to developing a comprehensive Road Transport Facility Information System (RTFIS) to enable efficient management and planning for sustainable development. Analogue record (maps and attributes) of the existing RTF were obtained from the relevant departments, and were updated with the data obtained through field and GPS surveys, and Google Earth image (2019). QGIS 3.8 software was used for Nearest Neighbor Analysis, developing comprehensive database and series of spatial and attributes queries in order to demonstrate the capability of Geospatial technology in efficient management of RTF information. The result revealed a dispersed distribution pattern of Roundabouts within the study area with nearest neighbor ratio of 1.3 and z-score value of 2.9. It is therefore recommended that the departments involved in RTF management should embrace Geospatial technology as one of the contemporary methods for efficient managing, manipulating, retrieving and updating RTF records for sustainable urban development.